Designing Interactive Learning Application Using Markerless Augmented Reality on Evolution of Atomic Theory Material - Zhafira Fanmita; Guspatni Guspatni (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
To increase student understanding and enrich the learning experience, research was conducted with the aim of designing a interactive learning application using markerless augmented reality as an interesting solution. This is because learning applications use augmented reality in evolution of atomic theory material into a form of education that combines innovative technology with personalized learning, so that it can help create a generation that is technologically skilled and ready to face future challenges. This research includes educational design research using Plomp development model, including preliminary research stage by doing the needs and context analysis, literature review, and theoretical framework and prototyping stage, including initial plan and self evaluation. For the results based on preliminary research data and the prototyping phase, it can be concluded that the design of learning applications using Plomp development model which produces prototype II that has been successfully run as expected according to the design based on the results of analysis in preliminary research. This application prototype is hoped to be continued to produce learning applications that can be used in schools to support chemistry learning.